Pengaruh Magang MBKM (Merdeka Belajar Kampus Merdeka) dan Efikasi Diri Terhadap Kesiapan Kerja Mahasiswa Universitas Sebelas Maret - Dirgantari, Dayu Oktavina; Indriayu, Mintasih; Sudarno, Sudarno (Universitas Batanghari Jambi, 2026)
This study aims to determine the effect of MBKM (Merdeka Belajar-Kampus Merdeka) internship and self-efficacy on work readiness in Sebelas Maret University students. This study is a quantitative descriptive study with a population of Sebelas Maret University students. The sampling technique was carried out by Purposive Sampling. Data collection was carried out using a questionnaire with a Likert scale. The validity test technique used product moment correlation, reliability test used Cronbach's alpha, data analysis used multiple linear regression analysis. The results of the study showed that there was a positive and significant influence between MBKM (Merdeka Belajar-Kampus Merdeka) internship and self-efficacy on work readiness in Sebelas Maret University students. The results of the F test analysis obtained a calculated F value (190.552) > F table (3.019) and a significance value of 0.000